A Way Towards Revamping Dynamic Capability Framework: A Coherent Approach Towards Superior Firm’s Performance - Ali Mazari, M. Rizwan (Journal of Applied Research and Multidisciplinary Studies, 2022)
The foremost objective of this paper is to revamp conceptual framework of Dynamic Capability based upon seminal paper of David Teece (2014), “The Foundations of Enterprise Performance: Dynamic and Ordinary Capabilities in an (Economic) Theory of Firms”. Previous research developments are aligned with this paper to enrich insight towards an advanced framework which may facilitate in attaining firm’s overall and sustainable advantage. This endeavor is unique in a sense that multiple related and effective constructs are added into the framework to avoid organizational inertia and it’s also aligned with the cognitive aspects of managerial leadership capabilities which was missing in previous researches. The former section entails introduction and theoretical underpinnings of Dynamic Capabilities framework. The later section covers logical definitions and descriptions of key concepts to get familiar with the framework. Finally, at the end, conceptual framework put forth along with conclusions.